Red Mountain No. 3 - Discovery Of The Ore Body, Ouray County, Colorado - James Matlock (Society for Mining, Metallurgy & Exploration, 1990)
The announcement of a minable reserve of 13.6 Mt (16 million tons) averaging 0.9 g/t (0.027 oz per ton) Au and 2.4 g/t (0.71 oz per ton) Ag for the open pit-heap leach reserve at Red Mountain No. 3 in Ouray County, Colorado, by Cornucopia Resources in November 1985 brings another open pit-heap leach precious metal ore body to the production stage. With about 8.2 Mt (9 million tons) of waste and metallurgical studies showing acceptable recovery rates, low reagent consumption, and good final percentage recovery, Red Mountain is a discovery that will add to the precious metal inventory of the US. Frank Baumgaruler of Denver, CO, recognized the precious metal potential in Red Mountain No. 3 and acquired all of the old claims. James Matlock conducted a field reconnaissance over Red Mountain No. 3 independently of the Baumgartner activities and recognized epithermal alteration and mineralization in the Tertiary volcanics. He recommended acquisition of the ground and was able to obtain rights and drill six core holes for Amoco in 1982. Amoco drilled a further nine core holes in 1983, but then dropped the property. Cyrano Resources examined the data and through its consulting geologist, V.F. Hollister, acquired the rights dropped by Amoco. In 1984 Cyrano began further drilling of the ore zone demonstrated by Amoco but they were then acquired by Cornucopia Resources. Cornucopia completed development of the property and commenced the permitting process in 1986. The property was recognized as a disseminated gold deposit by both Baumgartner and Matlock, and both deserve credit for properly evaluating mineralized outcrop in the Tertiary volcanics. However, Cornucopia recognized the profit potential in the heap leach exploitation of the ores and de- serves credit for completion of premine feasibility studies. The discovery is clearly a geological one, but the premine engineering studies were essential to the conversion of the prospect to a commercial mining enterprise. The deposit lies on the circular bounding fault of the Silverton caldera. Two reprints follow that help understand the geologic setting of the ore controls.